Changes in the Surface Roughness of Glass Ionomer Cement and Zirconomer after Immersion in Carbonated Beverages - Chair Effendi, Mohammad; Nugraeni, Yuli; Hartami, Edina; Nurul Ummah, Asma (UI Scholars Hub, 2020)
Nano glass ionomer cement (GIC) with nano zirconia as a raw material called zirconium is a newly developed type of restoration/tooth filling material that is used in dentistry. Objective: To examine the effect of carbonated beverages on the surface roughness of Zirconomer and GIC filling materials and determine if there was any difference between them. Methods: This is a true-experimental laboratory research study with a pre-posttest group design. The research samples consisted of 32 samples, 16 GIC samples and 16 Zirconomer samples, further divided into four time-sensitive groups: day 1, day 3, day 5, and day 7. The samples were immersed in artificial saliva and carbonated beverages for 24 hours. Surface roughness was measured using a surface roughness tester. Results: The average surface roughness from day 1 to day 7 of the GIC material immersed in carbonated beverages was 4.17 μm, which is higher than the average surface roughness of Zirconomer (3.091 μm), and the difference was significantly different (pConclusion: Zirconomer was found to be more resistant to carbonated beverages than GIC. There was a positive correlation between the length of immersion time in the carbonated beverages and the surface roughness of GIC and Zirconomer.